The Use of Picture Media to Enhance Students’ Writing Ability of Recount Text at MTs N 1 Kota Bengkulu - Hanura Febriani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
This study was carried out to improve the second year students’ writing ability through Picture Media at MTs N 01 of Bengkulu in academi year 2015/2016. The subjects of this study were consisted of 42 students. The method used in this study was Classroom Action Research (CAR). The Clasroom Action Research design applied in this study was a collaborative classroom action research. It mean that the researcher collaborated with the English teacher of MTs N 01 of Bengkulu as an observer and collaborator. The study was carried out in three cycles. Each cycle consisted of three meetings. The data were gathered in this study through field notes, and writing test. The result of the study showed that there was improvement of students’ writing ability. Most of the students gradually gained good scores at the end of each cycle. The score of Minimum Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English subject was 70 (seventy). In cycle 1, the result of the students’ score was poor. In cycle 2, the result of the students score has some progresses, and in the cycle 3 the result of the students score has improve effectively than action in cycle before were the mean score of students was in 75 (Good). In addition, there was a positive response from the English Teacher about implementing the action. In conclusion, Picture Media could solve the students’ problems and improve their writing ability.